1979
DOI: 10.1002/pssb.2220930121
|View full text |Cite
|
Sign up to set email alerts
|

On the Interaction between F‐ and α‐Centres in KBr

Abstract: Luminescence measurements show an increase in the F-centre lifetime in KBr, corresponding to a critical cc-centre concentration, after F-F' conversion. An inhibition of the luminescencc quenching effect, related t o the F-centre density, is also observed. The results are discussed in respect of the Crandall photoconductivity data and explained on the basis of an interaction mechanism that involves the electron capture cross-section by a-centres and the mean distance between F-centres.Par moyen des mesures de l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…I n successive experiments Bosi and Nimis [19,20] showed that in KBr there is an increase of the F-center lifetime corresponding to a critical a-center concentration after F -+ F' conversion; this lifetime increase is related to low and, in some cases, scarcely detectable critical a-center concentrations. These results were discussed in relation to the Crandallr211 photoconductivity data and explained on the basis of an interaction mechanism that involves the electron capture cross-section by a-centers and the mean distance between F-centers.…”
Section: Experimental Results and Discussioilmentioning
confidence: 99%
See 2 more Smart Citations
“…I n successive experiments Bosi and Nimis [19,20] showed that in KBr there is an increase of the F-center lifetime corresponding to a critical a-center concentration after F -+ F' conversion; this lifetime increase is related to low and, in some cases, scarcely detectable critical a-center concentrations. These results were discussed in relation to the Crandallr211 photoconductivity data and explained on the basis of an interaction mechanism that involves the electron capture cross-section by a-centers and the mean distance between F-centers.…”
Section: Experimental Results and Discussioilmentioning
confidence: 99%
“…The foregiving facts led the authors to the provocative hypothesis [20] that the zg, values might be non-intrinsic (at the lowest temperatures) because of the interaction between Fand a-centers in "real" crystals. On the other hand, it must be stressed that before works [19] and [20] the above mentioned experiments, ( I ) to (3), were never discussed within the framework of a univocal understanding of the nature of the F-center REX in A.H. It is only very recently that an effort has been made by Georgiev et al [27] to explain the effect (3) in terms of the low temperature ionization of the P-center RES through the lattice tunneling to low-lying ionization states in an endoor exothermic process.…”
Section: Experimental Results and Discussioilmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards the problem of the luminescence occurrence from F-centers in alkali halides, Bosi et al [ l l ] have discussed the validity of the models based o n the traditional Franck-Condon scheme, and have shown [12] [l, 12, 14, 151. Details of the experiments in KBr samples, containing F'-and a-centers, have been given in the previous papers [14,151 to which interested readers are referred. In particular, we started by considering the Crandall's photoconductivity experiments 1161 : when the reciprocal of the product of the conduction band lifetime, mobility and a-concentration is plotted versus the ratio NF/N, of the F-and a-densities, a straight line is obtained only if low F-density samples (1016 F/cm3) are used.…”
Section: Ham Et Al Tried To Explain All the Above Experi-mentioning
confidence: 99%
“…Crandall explained this difference on the basis of a-center cross-section (a,) overlap : in this way, the diameter of o, is equal to the critical distance between a-centers for the value NJN, at which the curves become non-linear. By using [14] Crandall data, for a sample containing 1.255 x lo1' F/cm3, we have found [15] the following relationship as a function of the temperature T : o, (cm2) = KT-', where K = 6 x 10-'and X = 3.40 f 0.08. In fact, Crandall infers that 0,overlap occurs at low T for every a-densities : for example, it appears for N, > 3 x 1014 cm-3 at 42 K (i.e., a practically undetectable concentration).…”
Section: Ham Et Al Tried To Explain All the Above Experi-mentioning
confidence: 99%